Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1587/transinf.2016ofp0004
|View full text |Cite
|
Sign up to set email alerts
|

Attribute Revocable Multi-Authority Attribute-Based Encryption with Forward Secrecy for Cloud Storage

Abstract: SUMMARYInternet of Things (IoT) has been widely applied in various fields. IoT data can also be put to cloud, but there are still concerns regarding security and privacy. Ciphertext-Policy Attribute-Based Encryption (CP-ABE) is attracted attention in cloud storage as a suitable encryption scheme for confidential data share and transmission. In CP-ABE, the secret key of a user is associated with a set of attributes; when attributes satisfy the access structure, the ciphertext is able to be decrypted. It is nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The scheme can efficiently attain multi-level privacy preservation without extra signatures. Nomura et al [25] proposed a multi-authority attribute-based encryption scheme with attribute revocation for cloud storage. It can revoke an attribute without updating a user's secret key.…”
Section: Related Workmentioning
confidence: 99%
“…The scheme can efficiently attain multi-level privacy preservation without extra signatures. Nomura et al [25] proposed a multi-authority attribute-based encryption scheme with attribute revocation for cloud storage. It can revoke an attribute without updating a user's secret key.…”
Section: Related Workmentioning
confidence: 99%
“…Let l denote the number of rows of the access matrix, |I| (|I| ≤ l) denote the number of rows used for decryption in the access matrix, P denote bilinear pair operation, and E denote exponential operation. In TABLE II, we found that the schemes in [16]- [18], [22] have no offline encryption mechanism, which cause the number of operations in encryption phase linearly increasing with l. In [16], [18], [22], the user directly decrypts the original ciphertext, so the exponential operations and the number of bilinear pair operations also linearly increase with |I| in the decryption phase, leading to high computational complexity. In the decryption process of vFAC, only one exponent operation is involved.…”
Section: Performance Analyses 1) Comparison Of Featuresmentioning
confidence: 99%
“…Therefore, the length of public/private key of AA is linearly related to |U |. The users private key in [16], [18], [20], [22] is directly generated by AA based on the user's attributes, so the length of private key is linearly related to |S|. When the number of attributes increases, the user's storage cost increases too.…”
Section: Performance Analyses 1) Comparison Of Featuresmentioning
confidence: 99%
See 2 more Smart Citations